Review on measurement techniques for drop size distribution in a stirred vessel - Zainal Abidin, M.I.I.; Abdul Raman, Abdul Aziz; Mohamad Nor, M.I. (American Chemical Society, 2013)
A literature review on measurements of drop size distribution in liquid−liquid dispersion produced in a stirred vessel is presented in this work. The methods of measurement can be classified into in situ and external measurement. Two main groups of measurement techniques, namely, a laser system and image analysis, are reviewed. Several issues regarding the applications of the techniques and possible ways to overcome the problems are discussed. The suitability of different techniques depends on the operating conditions and properties of the drops. Laser systems provide fast in situ measurements which are useful for online monitoring and detecting process changes but unable to deliver reliable drop size and distribution values. In situ image analysis techniques could give accurate measurement of drop size, but a long time is required to analyze drops from a large number of images. However with development of automated image analysis, analysis time can be reduced. Therefore real-time monitoring and process control by image analysis techniques can be possible.